APPLICATION OF E-COMMERCE LEARNING MODEL BASED ON E-PORTFOLIO TO GROW INTEREST OF STUDENTS IN ONLINE-BASED ENTREPRENEURSHIP IN DEPARTMENT OF COMMERCIAL ADMINISTRATION MALANG STATE POLYTECHNIC - Mohammad Maskan; Heru Utomo (Universitas muhammadiyah malang, 2021)
The learning approach so far at the State Polytechnic of Malang is more directed to teacher center learning (TCL). Currently, students can build their own knowledge in the learning process known as student center learning (SCL). In addition, the assessment of students is also more comprehensive and includes three aspects, namely: cognitive, affective and psychomotor. One such learning model is to use a portfolio approach. This is in accordance with the learning objectives of E-Commerce at the State Polytechnic of Malang given in semester 5, which emphasizes the achievement of these three aspects. The results show that E-Commerce learning based on E-Portfolio can raise enthusiasm for students, namely raising entrepreneurial attitudes and motivation and being able to understand the focus of the material discussed by lecturers in teaching, because the content and presentation of learning materials involves students actively and is combined with hands-on experience in the field.